2022
DOI: 10.3390/biom12091299
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone as an Anti-Inflammatory Drug and Immunomodulator: New Aspects in Hormonal Regulation of the Inflammation

Abstract: The specific regulation of inflammatory processes by steroid hormones has been actively studied in recent years, especially by progesterone (P4) and progestins. The mechanisms of the anti-inflammatory and immunomodulatory P4 action are not fully clear. The anti-inflammatory effects of P4 can be defined as nonspecific, associated with the inhibition of NF-κB and COX, as well as the inhibition of prostaglandin synthesis, or as specific, associated with the regulation of T-cell activation, the regulation of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 161 publications
1
34
0
Order By: Relevance
“…However, several studies have revealed the immunomodulatory effects of progesterone and progestin in the female genital tract and immune system. 56,57 Progesterone treatment tilts the Th1/Th2 balance toward Th2 58,59 and inhibits DC differentiation 60 In addition, we found that progesterone treatment prevents murine miscarriage via the suppression of IL-12 production by macrophages (manuscript in preparation). Therefore, we believe that progestins have no effect on surface markers or alamin production in our study; however, they may cause functional changes such as cytokine production in macrophages and other immune cells.…”
Section: Discussionmentioning
confidence: 80%
“…However, several studies have revealed the immunomodulatory effects of progesterone and progestin in the female genital tract and immune system. 56,57 Progesterone treatment tilts the Th1/Th2 balance toward Th2 58,59 and inhibits DC differentiation 60 In addition, we found that progesterone treatment prevents murine miscarriage via the suppression of IL-12 production by macrophages (manuscript in preparation). Therefore, we believe that progestins have no effect on surface markers or alamin production in our study; however, they may cause functional changes such as cytokine production in macrophages and other immune cells.…”
Section: Discussionmentioning
confidence: 80%
“…P4 activated an inhibitory G‐protein suggesting that mPRs are coupled to inhibitory G‐protein in Jurkat cells. These results suggest a potential novel mechanism for P4 immunoregulatory function through activation of mPRs 26,27 . P4‐induced blocking factor (PIBF) is a protein secreted by lymphocytes exposed to P4.…”
Section: Introductionmentioning
confidence: 88%
“…Variation in the expression of mPRs may influence P4 regulatory performance during pregnancy. PIBF increases in pregnant normal women compared to women who have experienced abortion 26,27 . P4 inhibits innate immune response by suppressing the activity of dendritic cells and macrophages by inhibiting the release of pro‐inflammatory cytokines by interfering with nuclear factor kappa B (NF‐κB) 28 .…”
Section: Introductionmentioning
confidence: 99%
“…This inflammatory phenotype may in part be due to the progressive decrease in circulating progesterone and Progesterone Induced Blocking Factor (PIBF) that occurs as normal pregnancies progress to parturition (Polgar et al, 2004;Hudic et al, 2016). Progesterone and PIBF both inhibit lymphocyte proliferation and inflammatory cytokine production, which potentially implicates them as important anti-inflammatory agents in the earlier portion of the pregnancy (Fedotcheva et al, 2022). Near the 37th week of pregnancy, PIBF decreases triggering increases in IL-1β and IL-6 along with decreases in the anti-inflammatory cytokines IL-1Ra and IL-9 (Polgar et al, 2004;Jarmund et al, 2021).…”
Section: Third Trimester Of Pregnancy and Parturitionmentioning
confidence: 99%